HIV-1 and HIV-2 differentially mature plasmacytoid dendritic cells into interferon-producing or antigen-presenting cells - Royle, Caroline M (J Immunol, 2014)
HIV-1 causes a progressive impairment of immune function. HIV-2 is a naturally attenuated form of HIV and HIV-2 patients display a slow-progressing disease. The leading hypothesis for the difference in disease phenotype between HIV-1 and HIV-2 is that more efficient T cell-mediated immunity allows for immune-mediated control of HIV-2 infection, similar to that observed in the minority of HIV-1-infected long-term non progressors. Understanding how HIV-1 and HIV-2 differentially influence the immune function may highlight critical mechanisms determining disease outcome. We investigated the effects of exposing primary human peripheral blood cells to HIV-1 or HIV-2 in vitro. HIV-2 induced a gene expression profile distinct from HIV-1, characterized by reduced type I interferon (IFN), despite similar up-regulation of IFN-stimulated genes and viral restriction factors. HIV-2 favoured plasmacytoid dendritic cell (pDC) differentiation into cells with an antigen-presenting cells (APC) phenotype rather than interferon-α-producing cells (IPC). HIV-2, but not HIV-1, inhibited IFN-α production in response to CpG-A. The balance between pDC maturation into IPC or development of an APC phenotype differentiates the early response against HIV-1 and HIV-2. We propose that divergent paths of pDC differentiation driven by HIV-1 and HIV-2 cause the observed differences in pathogenicity between the two viruses.